(untitled) (Res Medica, 2014)
The main aim of this research study was seen as a prototype to test the feasibility of a possible large scale project whose results could be used as a planning tool for provision of future facilities for the treatment and care of patients with sexually transmitted diseases. If fully developed, regular, possibly monthly figures might be produced which would aid the correlation of venereal disease incidence with that of other diseases and environmental factors, although ideas on these lines are at present essentially tentative.